2019
DOI: 10.1002/ece3.5269
|View full text |Cite
|
Sign up to set email alerts
|

Spatial differences in genetic diversity and northward migration suggest genetic erosion along the boreal caribou southern range limit and continued range retraction

Abstract: With increasing human activities and associated landscape changes, distributions of terrestrial mammals become fragmented. These changes in distribution are often associated with reduced population sizes and loss of genetic connectivity and diversity (i.e., genetic erosion) which may further diminish a species' ability to respond to changing environmental conditions and lead to local population extinctions. We studied threatened boreal caribou (Rangifer tarandus caribou) populations across their distribution i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 95 publications
(199 reference statements)
3
19
0
Order By: Relevance
“…It is made The copyright holder for this preprint this version posted December 30, 2020. ; https://doi.org/10.1101/2020.12.29.424772 doi: bioRxiv preprint were observed near the current southern edge of the boreal caribou range in Ignace, Ontario, suggesting recent isolation caused by range contraction. This result is congruent with the findings of a microsatellite study that suggested recent genetic erosion, a decrease in connectivity, and an increase in inbreeding along the southern continuous range edge of boreal caribou in Ontario and Manitoba (Thompson, Klütsch, Manseau, & Wilson, 2019). The second longest average ROH was observed on Michipicoten Island, Ontario, an isolated population that has experienced several recent bottlenecks (Bergerud et al, 2007;Fletcher, 2017).…”
Section: Inbreeding Historiessupporting
confidence: 84%
“…It is made The copyright holder for this preprint this version posted December 30, 2020. ; https://doi.org/10.1101/2020.12.29.424772 doi: bioRxiv preprint were observed near the current southern edge of the boreal caribou range in Ignace, Ontario, suggesting recent isolation caused by range contraction. This result is congruent with the findings of a microsatellite study that suggested recent genetic erosion, a decrease in connectivity, and an increase in inbreeding along the southern continuous range edge of boreal caribou in Ontario and Manitoba (Thompson, Klütsch, Manseau, & Wilson, 2019). The second longest average ROH was observed on Michipicoten Island, Ontario, an isolated population that has experienced several recent bottlenecks (Bergerud et al, 2007;Fletcher, 2017).…”
Section: Inbreeding Historiessupporting
confidence: 84%
“…We did not consider immigration or emigration in this model because they are low among boreal caribou populations (e.g. Thompson, Klutsch, Manseau, & Wilson, 2019), nor did we consider age-dependent effects due to the lack of information to parameterize such effects for boreal caribou.…”
Section: Aspatial Modelling Scenariosmentioning
confidence: 99%
“…However, many of these studies focused on populations more latitudinally centered in each subspecies' range. Investigations of genetic patterns in species populations, including in North American ungulates, have generally found genetic diversity to be lower at the margins and greater towards the center of a species' range (Eckert et al 2008;Thompson et al 2019). This is often due to isolation by distance or inbreeding as a result of multiple biotic and abiotic factors (i.e.…”
Section: Patterns Of Genetic Variation In Moosementioning
confidence: 99%